Pengaruh Lokasi Dan Promosi Terhadap Keputusan Pembelian Pada Heyho Eatery Di Jatinangor - Annisa Nur Fitriani (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This study aims to determine the influence of location and promotion on consumer purchasing decisions at Heyho Eatery Jatinangor. Amidst increasingly fierce competition in the culinary business, understanding consumer behavior is key to developing effective marketing strategies. The research method used was a quantitative approach. The sampling technique used was non-probability sampling with an accidental sampling approach, with questionnaires distributed to 98 respondents, who were visitors to the cafe. The data obtained were analyzed using multiple linear regression to determine the influence of each independent variable on the dependent variable. The results of the study indicate that location has a positive and significant influence on purchase decisions, promotion has a positive and significant influence on purchase decisions, and both location and promotion simultaneously have a significant effect on purchase decisions.